The Margaret Mitchell encyclopedia - Davis, Anita Price (McFarland & Company, Inc., Publishers, 2013)
"Atlanta writer Margaret Mitchell (1900-1949) wrote Gone With the Wind (1936), one of the best-selling novels of all time. The Pulitzer Prize-winning novel was the basis of the 1939 film, the first movie to win more than five Academy Awards. Margaret Mitchell did not publish another novel after Gone With the Wind. Supporting the troops during World War II, assisting African-American students financially, serving in the American Red Cross, selling stamps and bonds, and helping others--usually anonymously--consumed her. This book reveals little-known facts about her. The Margaret Mitchell Encyclopedia documents Mitchell's work, her life, her effect on Atlanta, the city's memorials to her, her residences, details of her death, information about her family, the establishment of The Margaret Mitchell House against great odds, and her relationships with the Daughters of the Confederacy and the Junior League. The book includes obscure photographs of the author from about 1902 to 1949"--Provided by publisher.